Stress and Female Reproductive System: Disruption of Corticotropin-Releasing Hormone/Opiate Balance by Sympathetic Nerve Traffic - Farideh Zafari Zangeneh (Tehran University of Medical Sciences, 2009)
Nowadays stress is an integral part of everyday living and the physiological and behavioral consequences of exposure to stressful situations have been extensively studied for decades. The stress response is a necessary mechanism but disrupts homeostatic process and it is sub served by a complex system located in both the central nervous system (CNS) and the periphery. Stressor-induced activation of the hypothalamus-pituitary-adrenal (HPA) axis and the sympathetic nervous system (SNS) results in a series of neural and endocrine adaptations known as the "stress response" or "stress cascade." The stress cascade is responsible for allowing the body to make the necessary physiological and metabolic changes required to cope with the demands of a homeostatic challenge. Normal activation of the HPA axis is essential for reproduction, growth, metabolic homeostasis, and responses to stress and they are critical for adapting to changes in the external environment. The regulation of gonadal function in men and women is under the control of the HPA. This regulation is complex and sex steroids are important regulators of GnRH and gonadotropin release through classical feedback mechanisms in the hypothalamus and the pituitary. The present overview focuses on the neuroendocrine infrastructure of the adaptive response to stress and its effects on the female reproductive system.